As obras para piano de Arthur Bosmans (1908-1991): por uma sonoridade brasileira - Gabriel Cursino Madeira Casara (2011)
The Belgium composer Arthur Bosmans has embarked on many different cultures printing through his music the many recollections of the places he has been. When he arrived in Brasil, in 1940, he initiated a series of works in pursuit of a Brazilian sonority that would honor the country he lived until the end of his life. This research takes up three of those works, written for piano solo: Toccata (1947), Cavaquinho Bem Temperado (1953) and Três Evocações (1982). They point out the elements that build his sonority and, through historical contextualization and analysis of his works, provides evidence for interpretational decisions